Elaboración de un juego didáctico de la diablada pillareña utilizando la técnica de cubeecraft para difundir el patrimonio cultural de Píllaro en los adolescentes de 12 a 16 años de la Unidad Educativa (t) Jorge Álvarez, durante el período 2014-2015 - Salazar Curco, Javier Edison (2015)
is developed from the need to disseminate the cultural heritage in adolescents with an educational purpose. This game is structured as a regulated game that includes moments of pre-reflexive action and symbolization or abstract- logic of what has been lived in order to achieve objectives of teaching curriculum, encouraging the development of creativity. For developing this game, we used methods such as descriptive and analytic and synthetic which served as the basis to analyze and provide solution to the investigation. We also used the descriptive research method and the bibliographic method. This allows collecting data and information of the place. The techniques of observation, survey and interview were used to collect information through a questionnaire which served for the development of the project....